2013
DOI: 10.1177/1363459312472082
|View full text |Cite
|
Sign up to set email alerts
|

Finding the patient in patient safety

Abstract: In the last decade, the field of patient safety has grappled with the complexity of health-care systems by attending to the activity of frontline clinicians. This article extends the field by highlighting the activity of patients and their carers in determining the safety of these systems. We draw on data from three studies exploring patients' accounts of their health-care experiences in Australia and internationally, to show how patients and carers are currently contributing to the safety of their own care. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 47 publications
(65 reference statements)
5
69
0
2
Order By: Relevance
“…Approaches to improving safety, which focus on implementing incident reporting systems, checklists and protocols, fail to address the patients' part in the negotiated process of healthcare and the importance of clinicians' benevolence in maintaining trust within the social-cultural context in which care takes place. Our results add further evidence to calls for the development of healthcare specific, rather than industry derived, approaches to inform and improve patient safety which embrace the patients' involvement in the negotiated process of healthcare (Hor, Godbold & Iedema, 2013;). …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Approaches to improving safety, which focus on implementing incident reporting systems, checklists and protocols, fail to address the patients' part in the negotiated process of healthcare and the importance of clinicians' benevolence in maintaining trust within the social-cultural context in which care takes place. Our results add further evidence to calls for the development of healthcare specific, rather than industry derived, approaches to inform and improve patient safety which embrace the patients' involvement in the negotiated process of healthcare (Hor, Godbold & Iedema, 2013;). …”
Section: Resultssupporting
confidence: 61%
“…Although many patients may be willing and able to monitor and protect their safety, success of their efforts is crucially dependent on clinicians' willingness to listen and act on the patients' concerns (Hor et al, 2013). Waring (2009) demonstrates how the construction of safety and harm in healthcare is contested terrain where, by intersubjective processes, knowledge is constructed and re-constructed to serve the interests of the various managerial and clinical stakeholders.…”
Section: Patient Safety and Trustmentioning
confidence: 99%
“…In general, though, the published evidence focuses on attitudes and expectations rather than on the opportunities for patient involvement in patient safety and the results of these. Some articles directly explore patient experiences of safety concerns Entwistle et al 2010), and a few consider their views on educational materials designed to involve them in safety issues (Schwappach and Wernli 2010;Rance et al 2013;Rainey et al Forthcoming;Pinto et al 2013;Hor et al 2013). In addition, a few studies use surveys and questionnaires to ascertain patients' willingness to be involved in direct challenge to professional practice, on issues such as hand hygiene, or their willingness to report adverse drug events (Pittet et al 2011), and one article discusses the use of patient feedback in real time (Hibbard et al 2005).…”
Section: The Literaturementioning
confidence: 99%
“…Vincent and Coulter (2002) have suggested that patients should be regarded as partners or co-producers in their care and argue that, without patient involvement, the patient safety movement is incomplete. Similarly, Hor et al (2013) have criticized the traditional model of patients as unreliable witnesses and the conceptualization of patient safety as something that resides in a set of actions external to the patient. Rather, they argue that safety is co-accomplished on an ongoing basis; patients are already taking responsibility for their care through their negotiations with clinicians.…”
Section: Should Patients Be Involved In Patient Safety?mentioning
confidence: 99%
See 1 more Smart Citation